ANALISIS PERBEDAAN ABNORMAL RETURN DAN LIKUIDITAS PERDAGANGAN SAHAM PADA PERUSAHAAN YANG MELAKUKAN REVERSE STOCK SPLIT YANG TERDAFTAR DI BEI - OKTAVIA, YANI (Jurnal Akuntansi AKUNESA, 2018)
This research aims to find out whether there are differences between abnormal return and stock trading liquidity before and after Reverse Stock split. All the companies used as sampling in this research has done Reverse stock split, and is listed in Bursa Efek Indonesia (BEI) trough 2002-2016. There are aproximately 40 companies listed during that period, however, this research only focus on 7 companies only because the other 33 companies does not fit the sampling requirements. This reseach use quantitative approach, especially history and causality type. For technique of data collections, this research use documentations method and using secondary data sources. This research will be using quantitative descriptive analysis by describing the calculations result. The datas then tested by hypothesis testing with normality test, followed by paired sample t-test using SPSS. The result of this research shown that there is no significant difference between abnormal return and stock trading liquidity before and after the reverse stock split.